The association between private tutoring and access to grammar schools: Voices of Year 6 pupils and teachers in south‐east England. (4th December 2019) - Hajar, Anas
Abstract : England has experienced recent growth in the prevalence of private tutoring (PT). The qualitative study reported in this article aims to explore the perceptions of 14 Year 6 pupils and their teachers from three state‐maintained primary schools in East Kent on PT participation and its impact on grammar school admissions. Data were collected through individual and focus group interviews and pupils' drawings. The data revealed that teachers were not totally aware of the scale of PT in their classes and ascribed PT merely to parental decision to prepare their child to pass the 11‐plus, grammar school entrance test. However, some pupils indicated that they shared in the decision to have PT, affirming that it was not only for 11‐plus test familiarisation and practice. PT also contributed to greater pupil confidence, involvement and enthusiasm for learning, together with improvement in social interactive skills (i.e. intangible benefits). Both teachers and pupils also explained the disadvantages of PT, including the psychological and financial burdens on the whole family and changing the playing field level. Teachers proposed some solutions to help Year 6 pupils without PT. From this qualitative study, pedagogical implications as well as areas for ongoing research are suggested.